Correlation between CYP11B2 polymorphism and the risk of preeclampsia. Issue 48 (25th November 2020) - Wang, Yan; Zhou, Minhua; Deng, Xun; Ma, Yanjiao; Jiang, Deqi
Abstract: Background: Many studies have evaluated the association between aldosterone synthase (CYP11B2) C-344T polymorphism and preeclampsia (PE) susceptibility, however, the results from different studies are inconsistent. Objective: The study aimed to derive a more precise estimation of this association. Methods: We searched PubMed, Embase, Chinese National Knowledge Infrastructure, China Biological Medicine, and Wanfang Database. The association was evaluated by calculating the odds ratios (ORs) with the corresponding 95% confidence intervals (CIs). Results: Seven case-control studies with a total of 720 cases and 766 controls were eligible to be included in this meta-analysis. Overall, there was no significant association between CYP11B2 C-344T polymorphism and PE (for the allele model T vs.C: OR=0.78, 95%CI 0.60-1.01, p=0.06; for the codominant model CT vs. CC: OR=1.08, 95%CI 0.80-1.46, p=0.63; for the dominant model TT + CT vs. CC: OR=0.91, 95%CI 0.68-1.20, p=0.49). Similar results were obtained in sensitivity analysis. Conclusion: In summary, the present meta-analysis suggests that CYP11B2 C-344T polymorphism may not be associated with genetic susceptibility of PE, but the association remains indeterminate due to the insufficient evidence. Abstract : Supplemental Digital Content is available in the text